Abnormal Activation of Tryptophan-Kynurenine Pathway in Women With Polycystic Ovary Syndrome - Wang, Siyu; Mu, Liangshan; Zhang, Chunmei; Long, Xiaoyu; Zhang, Yurong; Li, Rong; Zhao, Yue; Qiao, Jie (Frontiers in Endocrinology, 2022)
Background: Women with PCOS suffer from dysfunctional metabolism and studies have reported the increased levels of tryptophan in PCOS. However, the changes of downstream metabolites in tryptophan catabolism pathway remain unclear. Methods: This is a cross-sectional study included 200 PCOS patients and 200 controls who were recruited from the Reproductive Medicine Center of Peking University Third Hospital from October 2017 to June 2019. The PCOS patients and the control group were further divided into subtypes of normal weight and overweight/obesity, respectively. Fasting blood samples from all subjects were collected on days 2~3 of a natural menstrual cycle or when amenorrhea for over 40 days with follicle diameter not exceeding 10 mm. The plasma levels of tryptophan metabolites were quantitatively determined by the liquid chromatograph mass spectrometer, including tryptophan, serotonin, kynurenine, kynurenic acid, 3-hydroxykynurenine and quinolinic acid. Results: Tryptophan-kynurenine pathway was dysregulated in women with PCOS, with the significantly elevated levels of tryptophan, serotonin, kynurenine, kynurenic acid and quinolinic acid. Moreover, levels of tryptophan, kynurenine and kynurenic acid were positively correlated with luteinizing hormone, anti-Müllerian hormone, fasting insulin, HOMA-IR. tryptophan, kynurenine and quinolinic acid had obviously association with C-reactive protein levels. Furthermore, logistic regression showed that tryptophan, serotonin, kynurenine, kynurenic acid and quinolinic acid were all associated significantly with the increased risk of PCOS with adjustment for potential confounding factors. Additionally, tryptophan, kynurenine and kynurenic acid had well diagnostic performances for PCOS, and their combination exhibited higher sensitivity and specificity of diagnostic efficiency, with the area under the ROC curve of 0.824 (95% CI 0.777-0.871), which were comparable to the endocrine indicators. Conclusion (s): There exists abnormal activation of tryptophan-kynurenine metabolism in PCOS patients.